4E comparative analysis of energy transition scenarios for the decarbonization of a chocolate factory utilities in Brazil - Gonçalves, Audrey Novelli; Fonseca, Francisco Mello; Morawski, Alexandre Persuhn; de Faria, Pedro Rosseto; Santos, José Joaquim Conceição Soares (Frontiers in Chemical Engineering, 2025)
The government of the state of Espírito Santo, Brazil, has established that minimizing emissions, by considering the natural gas as the best fossil fuel during the energy transition period, and energy efficiency are two of the four strategies for industries to competitively achieve the energy transition and decarbonization. In this framework, a major chocolate factory currently meets its chilled-water demand with electricity from the national grid and its hot-water demand with natural gas boilers. This study evaluates alternative configurations based on the integration of Organic Rankine Cycle (ORC) and/or Vapor Compression Refrigeration (VCR) systems, simultaneously generating electricity, chilled water and/or hot water. Three scenarios are proposed and comparatively evaluated using a 4E (energy, exergy, environmental, and economic) assessment. Thermodynamic and environmental modeling of the current and proposed scenarios was conducted using nominal and operational data, with simulations performed in EES software. Mass, energy, and exergy balances were carried out, along with associated CO2 emissions. The economic analysis considered both operational costs and capital investments, the latter estimated through parametric equations for equipment sizing and costing. Feasibility indicators were applied, such as payback, net present value (NPV), and internal rate of return (IRR). The results indicate the VCR configuration, without ORC, as the most advantageous performance. This scenario requires an investment of US$ 2,679,612.19, resulting a payback period of 2 years and 3 months, an IRR of 51.40% and achieving the lowest CO2 emissions (0.467 ton/h) due to the elimination of natural gas boilers, using total electrification of the process. Given the relatively low emission factors of the Brazilian interconnected electric grid and the competitive electricity tariffs, electrification of industrial utilities emerges as the most promising decarbonization pathway. Specifically, in this case, VCR simultaneously produces chilled and hot water with high efficiency and reduced environmental impact. Building on the conclusion that electrification is the most favorable option, new insights for research opportunities arise. Future studies could investigate the use of Photovoltaic Thermal (PVT) hybrid solar collectors for the simultaneous production of electricity and hot water, thereby reducing emissions, as well as the integration of energy storage systems to further enhance emission reductions.